On the origin of Czech farkaš and čabraka - Tölgyesi, Tamás (Bohemica Olomucensia, 2018)
Hungarian farkas [fɒrkɒʃ] 'crupper' was most likely an adjective which was created from the noun fark 'tail' with the suffix -as. Instead of the expression farkas szíj 'strap under the (horse's) tail' was simply used farkas, which in the course of time was substantivised and borrowed into the Czech language.Czech čabraka, Slovak čabraka, čabrak, Polish czaprag 'saddlecloth' most probably come via Hungarian csáprág [ʧaːpraːg] from Turkish çaprak. German Schabracke, Czech šabrak, šabraka, Slovak šabrak, šabraka, Polish szabrak, szabraka and Slovenian šabraka forms were borrowed via Hungarian sabrák [ʃɒbraːk] from Turkish şaprak.
Keywords: Czech; Hungarian; borrowing; crupper; saddlecloth